How does agricultural land scale affect recycling behavior of agricultural wastes: evidence from CLES - Liu, Jing; Liu, Jin; Zhang, Huan; Zhou, Tianshu (Frontiers in Sustainable Food Systems, 2024)
The recycling of agricultural waste is an important measure for achieving green agricultural production. Existing studies have discussed the relationship between agricultural land scale and agricultural production from different angles, but ignored the disposal of agricultural waste. This study used China Land Economic Survey (CLES) from 2020 to 2021 and applied the probit model and the instrumental variable method to conduct the empirical analysis. The results showed a significant negative relationship between farmers' agricultural land scale and the recycling of agricultural waste. Heterogeneity analysis showed that the effect of less-developed areas was higher than that of relatively developed areas, and younger samples were less affected than the elderly. The mechanism analysis further pointed out that social norms and economic incentives can effectively promote the recycling of agricultural waste for farmers, given the scale of agricultural land. This study expands the relevant studies on agricultural waste disposal behavior, clarifies the impact and relevant mechanisms, and provides insights for realizing sustainable agricultural development.